Modeling and Control for a Blended Wing Body Aircraft A Case Study - Kozek, Martin; Schirrer, Alexander (Springer eBooks, 2015)
This book demonstrates the potential of the blended wing body (BWB) concept for significant improvement in both fuel efficiency and noise reduction and addresses the considerable challenges raised for control engineers because of characteristics like open-loop instability, large flexible structure, and slow control surfaces. This text describes state-of-the-art and novel modeling and control design approaches for the BWB aircraft under consideration. The expert contributors demonstrate how exceptional robust control performance can be achieved despite such stringent design constraints as guaranteed handling qualities, reduced vibration, and the minimization of the aircraft's structural loads during maneuvers and caused by turbulence. As a result, this innovative approach allows the building of even lighter aircraft structures, and thus results in considerable efficiency improvements per passenger kilometer. The treatment of this large, complex, parameter-dependent industrial control problem highlights relevant design issues and provides a relevant case study for modeling and control engineers in many adjacent disciplines and applications. Modeling and Control for a Blended Wing Body Aircraft presents research results in numeric modeling and control design for a large, flexible, civil BWB aircraft in the pre-design stage as developed within the EU FP7 research project ACFA 2020. It is a useful resource for aerospace and control engineers as it shows the complete BWB aircraft modeling and control design process, carried out with the most recent tools and techniques available. presents research results in numeric modeling and control design for a large, flexible, civil BWB aircraft in the pre-design stage as developed within the EU FP7 research project ACFA 2020. It is a useful resource for aerospace and control engineers as it shows the complete BWB aircraft modeling and control design process, carried out with the most recent tools and techniques available. Advances in Industrial Control aims to report and encourage the transfer of technology in control engineering. The rapid development of control technology has an impact on all areas of the control discipline. The series offers an opportunity for researchers to present an extended exposition of new work in all aspects of industrial control.